Boronic Acid-based Enzyme Inhibitors: A Review of Recent Progress - Fu, H.; Fang, H.; Sun, Jie; Wang, H.; Liu, A.; Sun, J.; Wu, Z. (Current Medicinal Chemistry, 2014)
Since Bortezomib was approved by US FDA as the first drug to treat multiple myeloma, various boronic acid compounds have been developed as enzyme inhibitors. This paper reviewed the progress of boronic acid-based inhibitors against enzymes including proteasome, serine protease, HDACs and other enzymes in the past decade.
Keywords: Boronic acid